Comparative immunogenicity of an mRNA/LNP and a DNA vaccine targeting HIV gag conserved elements in macaques - Valentin, Antonio; Bergamaschi, Cristina; Rosati, Margherita; Angel, Matthew; Burns, Robert; Agarwal, Mahesh; Gergen, Janina; Petsch, Benjamin; Oostvogels, Lidia; Loeliger, Edde; Chew, Kara W.; Deeks, Steven G.; et al. (Frontiers in Immunology, 2022)
Immunogenicity of HIV-1 mRNA vaccine regimens was analyzed in a non-human primate animal model. Rhesus macaques immunized with mRNA in lipid nanoparticle (mRNA/LNP) formulation expressing HIV-1 Gag and Gag conserved regions (CE) as immunogens developed robust, durable antibody responses but low adaptive T-cell responses. Augmentation of the dose resulted in modest increases in vaccine-induced cellular immunity, with no difference in humoral responses. The gag mRNA/lipid nanoparticle (LNP) vaccine provided suboptimal priming of T cell responses for a heterologous DNA booster vaccination regimen. In contrast, a single immunization with gag mRNA/LNP efficiently boosted both humoral and cellular responses in macaques previously primed by a gag DNA-based vaccine. These anamnestic cellular responses were mediated by activated CD8+ T cells with a phenotype of differentiated T-bet+ cytotoxic memory T lymphocytes. The heterologous prime/boost regimens combining DNA and mRNA/LNP vaccine modalities maximized vaccine-induced cellular and humoral immune responses. Analysis of cytokine responses revealed a transient systemic signature characterized by the release of type I interferon, IL-15 and IFN-related chemokines. The pro-inflammatory status induced by the mRNA/LNP vaccine was also characterized by IL-23 and IL-6, concomitant with the release of IL-17 family of cytokines. Overall, the strong boost of cellular and humoral immunity induced by the mRNA/LNP vaccine suggests that it could be useful as a prophylactic vaccine in heterologous prime/boost modality and in immune therapeutic interventions against HIV infection or other chronic human diseases.